Adjunct Faculty Training, Monitoring and Evaluation at the Department Level - John Griffith (Academic Chairpersons Conference Proceedings, 2018)
Improve the learning experience for students by improving performance of adjunct faculty. Learn the strategies and tools used by an award winning university to support adjunct faculty by: - Effective selection and faculty development - Departmental support at the course level - Providing effective mentoring and feedback
Keywords: adjunct faculty; faculty observation; faculty development; college/university instruction